Process standardization for guava tea - Manzanero, Lea Ivy Octaviano; Galvez, Flor Crisanta F. (1999., 2001)
Process standardization for guava tea was done by determining the maximum amount of tannin present in various tea infusions. Different guava tea infusions was prepared by boiling young leaves (terminal bud and the first two leaves closest to the buds) mature leaves (third and fourth levels), and old leaves for 10, 20, and 30 minutes. The tea infusions were analyzed for their tannin content following the AOAC procedure. Results showed that the tea infusions made from young leaves boiled for 30 minutes showed the highest amount of tannin. Its tannin content is 10.10% and is comparable with the amount of tannin teas available in the market. The acceptable level of tannin of commercial teas is 8% to 15%.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tea; Beverages